Examining the Digital Literacy Levels of Syrian Refugee University Students (International Journal of Scientific Research and Management (IJSRM), 2025)
The aim of this study is to examine the digital literacy levels of Syrian refugee students studying at universities in Turkey across different variables. A descriptive survey model was used in the research. The sample of the study consisted of 184 Syrian university students studying at Selçuk University in Konya. The "Student Information Form" and the "Digital Literacy Scale" were used as data collection tools. In the analysis of the data, independent sample t-tests and ANOVA analysis were conducted using the SPSS software package. According to the findings, the digital literacy levels of Syrian university students were found to be above average. The study concluded that there was no significant difference in digital literacy scores between male and female students. Additionally, the digital literacy scores of 4th-year students were found to be significantly higher than those of 1st-year students. An analysis of age groups revealed that the digital literacy scores of students aged 19-21 were significantly higher than those of students aged 25-27.